Perancangan Antarmuka Pengguna Sistem Informasi Manajemen Praktik Kerja Lapangan berbasis Mobile menggunakan Metode Human Centered Design di SMK Negeri 1 Sumenep - Dinda Ayu Ludfiana Safitri; Hanifah Muslimah Az-Zahra; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Internship is an activity organized by vocational schools to improve a particular field of expertise and prepare students to enter the world of work. PKL activities at SMK Negeri 1 Sumenep have three stages, namely planning/data collection, implementation, and assessment. The data collection stage to the assessment stage is still done manually which results in frequent gaps in data processing for street vendors. Therefore, at SMK Negeri 1 Sumenep need an information system for the management of street vendors activities. Before developing an information system, a user interface design is needed as a basic material or reference in system development. User interface design focuses on the appearance of a product and usability to increase the level of ease of display. One approach in designing user interfaces is Human Centered Design (HCD) which involves users in the process. The resulting user interface design is a display on the role of admin, street vendors committee, supervising teachers, and students. Usability evaluation uses the heuristic evaluation (HE) method which involves experts during the evaluation and by following usability principles. The results of usability testing on the user interface found a total of 11 problems from the evaluator.